Multifunctional nanoparticles confers both multiple inflammatory mediators scavenging and macrophage polarization for sepsis therapy - Wenjie Xi; Weijie Wu; Lili Zhou; Qi Zhang; Shushu Yang; Lihong Huang; Yijun Lu; Jing Wang; Xinjin Chi; Yang Kang (Materials Today Bio)
Sepsis is a serious and life-threatening condition, which can lead to organ failure and death clinically. Abnormally increased cell-free DNA (cfDNA) and inflammatory cytokines are involved in the development and progression of sepsis. Thus, cfDNA clearance and down-regulation of inflammatory factors are essential for the effective treatment of sepsis. Here we designed and constructed a polydopamine-based multifunctional nanoparticle for the treatment of sepsis. These nanoparticles (NPs) are composed of polydopamine (PDA) grafted with cationic polyethyleneimine (PEI). On the one hand, the NPs can utilize the electrostatic interaction to effectively adsorb cfDNA in blood, then effectively inhibiting the activation of toll like receptors (TLRs) and nuclear factor kappa B (NF-κB) pathways induced by cfDNA. On the other hand, the NPs have an immunomodulatory function, which can effectively convert pro-inflammatory macrophage (M1) into anti-inflammatory macrophage (M2), thus reduce the release of inflammatory cytokines and slow down the inflammatory storm of sepsis. In addition, the NPs possess good reactive oxygen species (ROS) scavenging ability. Briefly, the effective treatment of sepsis can be achieved by multiple strategies of effectively capturing the inflammatory triggering factor cfDNA, modulating the polarization of M1 macrophage to M2 macrophage and scavenging ROS, which has a promising clinical application.